Chaotic map technique for enhancement security for android mobile system based on image encryption - Kawther Thabt Saleh; Nisreen Abd Alhadi Jabr; Iman Hussein Al-Qinani (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Network security continues to be the priority of many organizations. To ensure the protection of their data, they pay great attention to Encryption systems. Moreover, because of the enormous developments in networks of connection particularly the internet which has used by several people to share a variety of data kinds. The security of data has been a significant issue. As a result, there is a significant focus in using methods of decryption and encryption. Numerous encryption techniques have become advanced to preserve data protection, chaotic encryption systems are one of these methods widely used in recent years, where several techniques were proposed to use a chaotic map for encrypt images for the reason that of their characteristics e.g., random action unpredictability and initial conditions sensitivity. In this paper, proof authentication of sent information is used chaotic encryption algorithm to provide cipher text and hidden in image then send to another user. This approach is applied in cellular operating system environment (android). Thus, the sending and receiving of text will be safe and secure. The proposed approach is tested on different types of mobile. The proposed system gives good results.